A study on the factors of local communities participation in local agenda 21: a case study in Majlis Bandaraya Melaka Bersejarah (MBMB) / Khadijah Khairudin - Khairudin, Khadijah (Faculty of Administrative Science and Policy Studies, 2011)
The rapid global developments become an addiction of every single government nowadays. As a result, the issue of sustainable development in every country becomes crucial. Agenda 21 is a global sustainable action plan which focuses on individuals within the community, and specifically, within local government to shape the lives of communities. It is a mandates of the local authority to be responsible in this new phenomenon to enhance public participation. It is to ensure that the agenda meets the objective. The thrust of this study is directed towards answering the question regarding several factors that lead to the local communities’ participation in LA21 program where it is conducted at Melaka Tengah, which is the area that under the authority of Majlis Bandaraya Melaka Bersejarah (MBMB). The researcher had used the convenient sampling technique which selects 100 people as the respondents. From this study, it is found that all the factors listed have a significant relationship with participation where all the factors can lead to communities’ participation in LA21.